Paganini: la vita, le opere, il suo tempo - Prefumo, Danilo 1953-; Dellaborra, Mariateresa (Lucca Libreria musicale italiana, 2020)
Niccolò Paganini (Genoa, 1782 - Nice, 1840) was one of the absolute protagonists of 19th-century European music, a symbol of Romantic instrumental virtuosity, a daring renewer of violin technique, a skilful guitarist and a prolific composer. Trained in his hometown and essentially self-taught, he first made his name in Italy and then, starting in 1828, throughout Europe, during a memorable tour that ended in 1834 after having toured the main musical centres of Austria, Bohemia, Poland, Germany, France, Great Britain and Belgium. Freeing him at last from the incrustations of almost always unfounded inferences and rumours that made Paganini a mysterious and bewildering character, the volume gives in the first part a clear biographical profile based on the most recent historical research. This is followed by a wide-ranging and detailed analysis of all his works, conducted with the declared intention of contextualising Paganini's technique and musical style within his own era, noting the multiple, and often ignored, relationships that bound him to violinist-composers of the past (above all Locatelli and Lolli) and present, and in particular to the great masters of the French school contemporary to him: Giovanni Battista Viotti, Pierre Rode and Rodolphe Kreutzer. (Translated with DeepL.com)
Includes bibliographical references (pages 343-357) and index
Keywords: Paganini, Niccolò -- 1782-1840